Broad‐substrate screen as a tool to identify substrates for bacterial Gcn5‐related N‐acetyltransferases with unknown substrate specificity. (17th December 2012) - Kuhn, Misty L.; Majorek, Karolina A.; Minor, Wladek; Anderson, Wayne F.
Abstract: Due to a combination of efforts from individual laboratories and structural genomics centers, there has been a surge in the number of members of the Gcn5‐related acetyltransferasesuperfamily that have been structurally determined within the past decade. Although the number of three‐dimensional structures is increasing steadily, we know little about the individual functions of these enzymes. Part of the difficulty in assigning functions for members of this superfamily is the lack of information regarding how substrates bind to the active site of the protein. The majority of the structures do not show ligand bound in the active site, and since the substrate‐binding domain is not strictly conserved, it is difficult to predict the function based on structure alone. Additionally, the enzymes are capable of acetylating a wide variety of metabolites and many may exhibit promiscuity regarding their ability to acetylate multiple classes of substrates, possibly having multiple functions for the same enzyme. Herein, we present an approach to identify potential substrates for previously uncharacterized members of the Gcn5‐related acetyltransferase superfamily using a variety of metabolites including polyamines, amino acids, antibiotics, peptides, vitamins, catecholamines, and other metabolites. We have identified potential substrates for eight bacterial enzymes of this superfamily. This information will be used to further structurally and functionally characterize them.